Sumienie naukowe i kryzys niezależności uczonych = Scientific conscience and the crisis of scientists` independence - Dudek, Joanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author analyzes the topicality and sense of the term "scienti?c conscience" in the context of the ethos of scientists. Based on the literature, the author refers to the traditions of ethos, professional ethics and moral philosophy in order to establish whether conscience as a form of self-assessment and self-control in decision making and in valuation of actions plays an important role as a part of scientists` professional and moral conscience. The theoretical ?ndings are confronted with the content of three documents regulating the ethics framework for scientists, which have appeared in the Polish science within the last twenty-?ve years. The article notices the phenomenon of departure from the tradition of being driven by one`s own undivided and independent conscience in playing professional roles. The phenomenon of "vanishing conscience" in scienti?c practice is understood by the author as a sign of scientists` resignation from their independence in favour of giving in to extra-scienti?c mechanisms.
Keywords: sumienie naukowe; etos; etyka zawodowa; niezależność; prawda; scientific conscience; ethos; professional ethics; independence; truth